High yield purification of an isoleucine zipper-modified CD95 ligand for efficient cell apoptosis initiation and with biotin or DNA-oligomer binding domain to probe ligand functionalization effects - Xiaoyue Shang; Nina Bartels; Johann Moritz Weck; Sabine Suppmann; Jérôme Basquin; Gajen Thaventhiran; Amelie Heuer-Jungemann; Cornelia Monzel (BMC Biotechnology)
Abstract Background Cluster of differentiation 95 (CD95/Fas/Apo1) as part of the Tumor-necrosis factor (TNF) receptor family is a prototypic trigger of the ‘extrinsic’ apoptotic pathway and its activation by the trimeric ligand CD95L is of high interest. However, CD95L, when presented in solution, exhibits a low efficiency to induce apoptosis signaling in human cells. Results Here, we design a recombinant CD95L exhibiting an isoleucine zipper (IZ) motif at the N-terminus for stabilization of the trimerized CD95L and demonstrate its high apoptosis initiation efficiency. This efficiency is further enhanced by antibody-mediated crosslinking of IZ-CD95L.A cysteine amino acid fused behind the IZ is used as a versatile coupling site for bionanotechnological applications or for the development of biomedical assays. A fast, cheap, and efficient production of CD95L via the HEK293T secretory expression system is presented, along with CD95L affinity purification and functionalization. We verified the biological activity of the purified protein and identified a stabilized trimeric CD95L structure as the most potent inducer of apoptosis signaling. Conclusions The workflow and the findings reported here will streamline a wide array of future low- or high-throughput TNF-ligand screens, and their modification towards improving apoptosis induction efficiency and, potentially, anticancer therapy.